Vascular malformations of the lungs and the liver at patient with hereditary hemorrhagic teleangiectasia - M. S. Zharkova; A. V. Lapshin; Ye. N. German; M. V. Mayevskaya; I. A. Sokolina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To show a rare case of pulmonary and hepatic vascular malformations development, to discuss pathophysiological mechanisms of revealed changes and clinical symptoms of disease.Features of clinical case. At the young patient disease manifested by nasal bleedings, that was subsequently accompanied by severe respiratory failure and portal hypertension. Clinical signs were related to skin and mucosae teleangiectasias, diffuse small vascular malformations of the liver and lungs with left-toright shunting of the blood. Difficulty of medical tactics choice was determined by impossibility of conservative treatment, vascular embolization or organ-preserving resection of lobe of the organ. Patient has been referred to inclusion to the Waiting list for the lungs and liver transplantation.Conclusion. Hereditary hemorrhagic teleangiectasia is infrequent genetic disease described by anomaly of vascular development and diversity of clinical symptoms. Despite of the better comprehension of mechanisms of disease and introduction of new methods of its diagnostics, hereditary hemorrhagic teleangiectasia is not completely estimated by clinicians, frequently remaining unrecognised, up to development of severe, sometimes — life-threatening states.